2017
DOI: 10.1002/berj.3289
|View full text |Cite
|
Sign up to set email alerts
|

Information and choice of A‐level subjects: A cluster randomised controlled trial with linked administrative data

Abstract: We estimated the effects of an intervention which provided information about graduate wages to 5593 students in England, using a blinded cluster randomised controlled trial in 50 schools (registration: AEARCTR‐0000468). Our primary outcome was students’ choice of A‐level subjects at age 16. We also recorded the students’ expectations of future wages and the A‐level subjects they intended to take before and after the intervention, and linked their data into national administrative school examination records. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…They mostly provide information on the costs of, and returns to, different kinds of education and test its effect on HE intentions and decisions (e.g., Barone, Schizzerotto, Abbiati, & Argentin, 2017;McGuigan et al, 2016;Oreopoulos & Dunn, 2013). Although some studies also look at the impact of information on major choices (Barone et al, 2019;Hastings et al, 2015;Kerr et al, 2015;Wiswall & Zafar, 2015a, b; for A-level choices see Davies et al, 2017), most of them do not differentiate their analysis by gender.…”
Section: Income Information and Major Choice: Findings From Experimenmentioning
confidence: 99%
See 1 more Smart Citation
“…They mostly provide information on the costs of, and returns to, different kinds of education and test its effect on HE intentions and decisions (e.g., Barone, Schizzerotto, Abbiati, & Argentin, 2017;McGuigan et al, 2016;Oreopoulos & Dunn, 2013). Although some studies also look at the impact of information on major choices (Barone et al, 2019;Hastings et al, 2015;Kerr et al, 2015;Wiswall & Zafar, 2015a, b; for A-level choices see Davies et al, 2017), most of them do not differentiate their analysis by gender.…”
Section: Income Information and Major Choice: Findings From Experimenmentioning
confidence: 99%
“…Research has shown that students often have incorrect expectations about income returns to higher education (HE) (e.g., Hastings, Neilson, & Zimmermann, 2015;Oreopoulos & Dunn, 2013). Correspondingly, experimental research shows that providing detailed information on various, often monetary outcomes "nudges" students to make better informed and thus partly different educational choices (e.g., Davies, Davies, & Qiu, 2017;Domina, 2009;Hastings et al, 2015;McGuigan, McNally, & Wyness, 2016). Even though evidence is inconsistent (see Herbaut & Geven, 2019 for a review), some studies reveal that additional financial information on HE especially increases the college intentions, applications, or attendance of students from socially disadvantaged families (or from broader disadvantaged contexts) (e.g., Loyalka, Song, Wei, Zhong, & Rozelle, 2013;Oreopoulos & Dunn, 2013;.…”
Section: Introductionmentioning
confidence: 99%